2008
DOI: 10.1007/bf03021492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propofol on hepatic blood flow and oxygen balance in rabbits

Abstract: reports of original investigations CAN J ANESTH 55: 6 www.cja-jca.org June, 2008 Purpose: Propofol has been reported to alter hepatic blood flow and to increase hepatic oxygen consumption. This study was designed to determine the effect of propofol on hepatic blood flow and oxygenation in rabbits, in order to establish its net effect on hepatic oxygen balance.Methods: Twenty, adult male, New Zealand white rabbits were randomly divided into two groups: Group P (propofol, 0.6 mg·kg). An electromagnetic flowme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…Our finding of higher hepatic blood flow during propofol compared with desflurane anaesthesia is supported by two studies in animals that have demonstrated a dose‐dependant increase in total hepatic blood flow under continuous propofol administration [5, 8]. Using a rat model, Carmichael et al.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our finding of higher hepatic blood flow during propofol compared with desflurane anaesthesia is supported by two studies in animals that have demonstrated a dose‐dependant increase in total hepatic blood flow under continuous propofol administration [5, 8]. Using a rat model, Carmichael et al.…”
Section: Discussionsupporting
confidence: 62%
“…The increase in hepatic blood flow was based on an increase in both hepatic arterial and portal venous blood flows. Recently, it has been shown that propofol‐increased hepatic blood flow in rabbits [8]. Interestingly, in both of these studies, the propofol‐induced increase in liver blood flow was associated with an increase in hepatic oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Nyman et al (2005) reported a faster time to peak enhancement of contrast agent in the liver of propofol-treated animals compared to awaken, conscious dogs. However, propofol affects the cardiocirculatory system (Langley & Heel 1988), increasing hepatic blood flow (Wouters et al 1995;Zhu et al 2008). The dose of propofol used in the study of Nyman et al (2005) was not mentioned, thus no further comparisons with our results are possible.…”
Section: Figurementioning
confidence: 79%
“…The lack of a protective effect of propofol in an in vitro liver model might be because of the use of oxygen during its own metabolism, resulting in an oxygenation debt. In contrast, in vivo, the increase in hepatic oxygen consumption by propofol is fully compensated for by an increased oxygen supply owing to increased hepatic blood flow in rat [35] and rabbit models [36]. There is good evidence that vasodilators protect against I/R injury by improving hepatic blood flow and thus maintaining an oxygen balance and energy metabolism [37].…”
Section: Discussionmentioning
confidence: 99%